Electrical characterization of phytoplankton suspensions using impedance spectroscopy - Margaret R. Jett; Mohamed Z. Rashed; Susan P. Hendricks; Stuart J. Williams (Journal of Applied Phycology, 2021)

The dependence of synchrony on timescale and geography in freshwater plankton - Thomas L. Anderson; Lawrence W. Sheppard; Jonathan A. Walter; Susan P. Hendricks; Todd D. Levine; David S. White; Daniel C. Reuman (Limnology and Oceanography, 2019)
Spatial synchrony is defined by related fluctuations through time in population abundances measured at different locations. The degree of relatedness typically declines with increasing distance between sampling locations. Standard approaches for assessing synchrony assume isotropy in space and uniformity across timescales of analysis, but it is now known that spatial variability and timescale structure in population dynamics are common features. We tested for spatial and timescale structure in the patterns of synchrony of freshwater plankton in Kentucky Lake, U.S.A. We also evaluated whether different mechanisms may drive synchrony and its spatial structure on different timescales. Using wavelet techniques and matrix regression, we analyzed phytoplankton biomass and abundances of seven zooplankton taxa at 16 locations sampled from 1990 to 2015. We found that zooplankton abundances and phytoplankton biomass exhibited synchrony at multiple timescales. Timescale structure in the potential mechanisms of synchrony was revealed primarily through networks of relationships among zooplankton taxa, which differed by timescale. We found substantial interspecific variability in geographic structures of synchrony and their causes: all mechanisms we considered strongly explained geographic structure in synchrony for at least one species, while Euclidean distance between sampling locations was generally less well supported than more mechanistic explanations. Geographic structure in synchrony and its underlying mechanisms also depended on timescale for a minority of the taxa tested. Overall, our results show substantial and complex but interpretable variation in structures of synchrony across three variables: space, timescale, and taxon. It seems likely these aspects of synchrony are important general features of freshwater systems.

Ecosystem respiration: Drivers of daily variability and background respiration in lakes around the globe - Christopher T. Solomon; Denise A. Bruesewitz; David C. Richardson; Kevin C. Rose; Matthew C. Van de Bogert; Paul C. Hanson; Timothy K. Kratz; Bret Larget; Rita Adrian; Brenda Leroux Babin; Chih-Yu Chiu; David P. Hamilton; et al. (Limnology and Oceanography, 2013)
We assembled data from a global network of automated lake observatories to test hypotheses regarding the drivers of ecosystem metabolism. We estimated daily rates of respiration and gross primary production (GPP) for up to a full year in each lake, via maximum likelihood fits of a free‐water metabolism model to continuous high‐frequency measurements of dissolved oxygen concentrations. Uncertainties were determined by a bootstrap analysis, allowing lake‐days with poorly constrained rate estimates to be down‐weighted in subsequent analyses. GPP and respiration varied considerably among lakes and at seasonal and daily timescales. Mean annual GPP and respiration ranged from 0.1 to 5.0 mg O 2 L −1 d −1 and were positively related to total phosphorus but not dissolved organic carbon concentration. Within lakes, significant day‐to‐day differences in respiration were common despite large uncertainties in estimated rates on some lake‐days. Daily variation in GPP explained 5% to 85% of the daily variation in respiration after temperature correction. Respiration was tightly coupled to GPP at a daily scale in oligotrophic and dystrophic lakes, and more weakly coupled in mesotrophic and eutrophic lakes. Background respiration ranged from 0.017 to 2.1 mg O 2 L −1 d −1 and was positively related to indicators of recalcitrant allochthonous and autochthonous organic matter loads, but was not clearly related to an indicator of the quality of allochthonous organic matter inputs.

Calcitonin is expressed in the chicken pituitary gland: influence of gonadal steroids and sexual maturation - Sreenivasa R. Maddineni; Susan M. Krzysik-Walker; Olga M. Ocón-Grove; Susan M. Motch; Gilbert L. Hendricks; Ramesh Ramachandran (Cell and Tissue Research, 2007)

Biochemical Model for Inflammation of the Brain: The Effect of Iron and Transferrin on Monocytes and Lipid Peroxidation - Susan J. van Rensburg; Johann van Zyl; Dinie Hon; Willie Daniels; Jacobus Hendricks; Felix Potocnik; Rajiv Erasmus (Metabolic Brain Disease, 2004)

A Mechanism for Zinc Toxicity in Neuroblastoma Cells - Willie M. U. Daniels; Jacobus Hendricks; Ruduwaan Salie; Susan J. van Rensburg (Metabolic Brain Disease, 2004)

Factors regulating autotrophy and heterotrophy in the main channel and an embayment of a large river impoundment - Paul A. Bukaveckas; John Jason Williams; Susan P. Hendricks (Aquatic Ecology, 2002)

Evidence that hyporheic zones increase heterotrophic metabolism and phosphorus uptake in forest streams - Patrick J. Mulholland; Erich R. Marzolf; Jackson R. Webster; Deborah R. Hart; Susan P Hendricks (Limnology and Oceanography, 1999)